PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 5 PARIAMAN - Ardi, Nanda Safira (Departemen Matematika, 2025)
This study explores the effectiveness of the Think Talk Write (TTW) cooperative learning model in enhancing students’ understanding of mathematical concepts. Mathematics education aims to help students connect prior knowledge with new material and apply it in problem-solving. However, low understanding of concepts is still a challenge due to limited student involvement and ineffective learning models. Using a non-equivalent post-test only control group design, the research was conducted on eighth-grade students at SMP Negeri 5 Pariaman in the 2024/2025 academic year. The results showed p-value of 0.000 at a 0.05 significance level, leading to the rejection of H0. Thus, the TTW model proves to be more effective than the conventional model in improving students’ mathematical understanding. Keyword Conventional Learning Model, Mathematics Conceptual Understanding, TTW Model